2021
DOI: 10.1051/e3sconf/202123201026
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Motivation In Organic Rice Farming In Gempol Village, Karanganom District, Klaten Regency

Abstract: Organic rice innovation has several advantages, such as a higher selling price, better health aspect, and environmentally friendly, and more and more farmers are interested in innovating. There is a government policy to develop it. Farmers plant organic rice because they have motivation. This motivation study utilized Maslow’s needs theory, intending to describe the motivation of farmers in organic rice farming in Gempol Village, Karanganom, Klaten. The data were analyzed descriptively using scoring techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The results showed that the empowerment factor from the organizational culture aspect had a readiness level of 83.2% (Table 3). The four variables of organizational culture aspects are represented by values, namely collaboration, trust, learning processes, and group leadership to realize organic farming [35]. This shows the highest organizational culture readiness within the farmer group.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the empowerment factor from the organizational culture aspect had a readiness level of 83.2% (Table 3). The four variables of organizational culture aspects are represented by values, namely collaboration, trust, learning processes, and group leadership to realize organic farming [35]. This shows the highest organizational culture readiness within the farmer group.…”
Section: Resultsmentioning
confidence: 99%
“…In matters of religion, the farmers also believe that life is to undergo a command from God, which means that everything in life depends on God's will and gifts (Dharmawan, 2018). In harmony, Indardi and Nugroho (2021) state that the high need for belongingness and love is formed by interacting with others, expanding social relationships, and working together. The researchers, therefore, conclude that the salt farmers have successfully satisfied their needs of belongingness and love.…”
Section: The Satisfaction Of the Salt Farmers' Basic Needs Based On M...mentioning
confidence: 99%